Integration of AI and OR techniques in constraint programming : 14th International Conference, CPAIOR 2017, Padua, Italy, June 5-8, 2017, Proceedings /: 14th International Conference, CPAIOR 2017, Padua, Italy, June 5-8, 2017, Proceedings. (2017) - Unknown
No abstract available